2020
DOI: 10.1007/s12265-020-10025-4
|View full text |Cite
|
Sign up to set email alerts
|

A Toolbox of Potential Immune-Related Therapies for Inflammatory Cardiomyopathy

Abstract: Myocarditis is a multifactorial disorder, characterized by an inflammatory reaction in the myocardium, predominantly triggered by infectious agents, but also by antigen mimicry or autoimmunity in susceptible individuals. Unless spontaneously resolved, a chronic inflammatory course concludes with cardiac muscle dysfunction portrayed by ventricular dilatation, clinically termed inflammatory cardiomyopathy (Infl-CM). Treatment strategies aim to resolve chronic inflammation and preserve cardiac function. Beside st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 146 publications
0
10
0
Order By: Relevance
“…Inflammation is an important driver of HF, by which its role in the pathogenesis of HFrEF and HFpEF differs (133,134). Although it plays a pathological role in the EAT of obese patients (46), pharmacological treatment with anti-inflammatory agents like steroids (135) cannot be recommended in HF patients with DM and/or metabolic syndrome (136). Theoretically, several biological agents like interleukin (IL)-1 and IL-6 inhibitors can target EAT-induced myocardial inflammation (136).…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is an important driver of HF, by which its role in the pathogenesis of HFrEF and HFpEF differs (133,134). Although it plays a pathological role in the EAT of obese patients (46), pharmacological treatment with anti-inflammatory agents like steroids (135) cannot be recommended in HF patients with DM and/or metabolic syndrome (136). Theoretically, several biological agents like interleukin (IL)-1 and IL-6 inhibitors can target EAT-induced myocardial inflammation (136).…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…Although it plays a pathological role in the EAT of obese patients (46), pharmacological treatment with anti-inflammatory agents like steroids (135) cannot be recommended in HF patients with DM and/or metabolic syndrome (136). Theoretically, several biological agents like interleukin (IL)-1 and IL-6 inhibitors can target EAT-induced myocardial inflammation (136). The small D-HARD study has demonstrated the beneficial effects of the competitive IL-1 receptor antagonist anakinra in HFpEF patients (137).…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…A panel of different (anti‐)inflammatory and (anti‐)fibrotic network systems including macrophages, B and T cells, 8,16–18 platelets, 19 myofibroblasts, 20,21 cytokines, 22–24 chemokines, 25 damage‐associated molecular patterns, 26–30 soluble ST2, 31 lysyl oxidase‐like 2, 18 galectin‐3, 32 matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMP) 33,34 as well as aldosterone, 24,35 play a major role in the defence and healing process under these circumstances. For most of these potential targets, with the exception of aldosterone, no well‐established therapeutic strategies are available, and no direct translation into the clinic is possible 36 . In an animal study, aldosterone infusion has been shown to induce ventricular hypertrophy and interstitial fibrosis in both right and left ventricles 37 .…”
Section: Introductionmentioning
confidence: 99%
“…For most of these potential targets, with the exception of aldosterone, no well-established therapeutic strategies are available, and no direct translation into the clinic is possible. 36 In an animal study, aldosterone infusion has been shown to induce ventricular hypertrophy and interstitial fibrosis in both right and left ventricles. 37 Further studies have suggested that aldosterone-induced generation of reactive oxygen species and low-grade inflammation underlie aldosterone-induced cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic inflammatory reaction in myocarditis can, when progressed into a state of chronic inflammation, result in outward remodeling and loss of cardiac function, which is clinically referred to as inflammatory cardiomyopathy (Infl-CM). Elsanhoury and colleagues describe that Infl-CM remains an unmet medical need [8]. Several therapeutic targets, revealed by basic research, still lack translation to the patient.…”
mentioning
confidence: 99%